Ratification of the Contract across the Carried Phone (Mobile) for the Financial Treatments in the Islamic Doctrine - Rasheed Ali, Mikael (Journal of Duhok University, 2019)
This is the type of the contract by the mobile phone (mobile) is one of the contemporary contracts that are in need is essential to the research and statement of where the jurisdiction of this species of contracts, so as to spread all over the world , and declined direct meeting  between the two sides of the contractors because of new technologies, especially those transactions that reached our country and practiced by scientists and other people and treat them with all industrial and commercial countries like Dubai, China, Malaysia and others.In view of the prevalence of e-contract via mobile phone (mobile) in the world today between all people old and young, effortlessly connecting , this type of contract is not found in the time of the Revelation, and this does not mean that such as crisp, because the Islamic jurisprudence did not stand    in front of the dramatic developments that occur in every era of innovations and discoveries inventions modern techniques, to reconsider and research prognostication and jurisprudence, according to the Book of Allah (Quran ) and the Sunna of His Messenger, intercourse, measurement and interest considered as correct and custom and the implications of this, which is open to people wide horizons in dealing, and raises raises  their embarrassment and discomfort in the right way. To know the provisions of the contracts of new financial transactions, So Islamic law does not deprive the innovation and invention modern self-esteem, but denied that the irregularities were contrary to the purposes of the Islamic law, and when these techniques were forbidden, the Islamic law does not see anything wrong in use and their contracts. Therefore, this research aims to describe the ruling for a contract mobile.